Older Workers and Labour Market Exclusion Processes A Life Course perspective - Burnay, Nathalie; Ogg, Jim; Krekula, Clary; Vendramin, Patricia (Life Course Research and Social Policies, 2023)
This open access book addresses the important and neglected question of older workers who are excluded from the labour market. It challenges post-capitalist discourses of active ageing with a focus on restrictive end-of-career and retirement measures. The book demonstrates how a paradigm shift is generating real processes of exclusion for important sectors of the population. By providing strong empirical evidence from different contexts, the impact of different life course trajectories on the risks and the opportunities at the end of career are demonstrated. The organisation of workplace and institutional frameworks which reinforce inequalities are also presented. As such the book is an essential reading for students, academics and policy makers who seek to understand how exclusion processes operate to the disadvantage of older workers in the labour market.